A Review on the Application of Molecular Dynamics to the Study of Coalbed Methane Geology - Yu, Song; Bo, Jiang; Chongtao, Wei; Xuguang, Dai; Fangkai, Quan; Chenliang, Hou; Guoxi, Cheng (Frontiers in Earth Science, 2021)
Since the last three decades, molecular dynamics (MD) has been extensively utilized to the field of coalbed methane geology. These include but not limited in 1) adsorption of gaseous molecules onto coal, 2) diffusion of gaseous molecules into coal, 3) gas adsorption induced coal matrix swelling and shrinkage, and 4) coal pyrolysis, and combustion. With the development of the computation power, we are entering a period where MD has been widely used for the above higher level applications. Here, the application of MD for coalbed methane study was reviewed. Combined the GCMC (grand canonical Monte Carlo) and MD simulation can provide the microscopic understanding of adsorption of gaseous molecules onto coal. The experimental observations face significant challenges when encountering the nanoscale diffusion process due to coal structure heterogeneity. Today, all types of the diffusion coefficients can be calculated based on MD and Peng-Robinson equation. To date, the MD simulation for both pure and multicomponents has reached a situation of unprecedented success. Meanwhile, the swelling deformation of coal has been attracting an increasing attention both via the experimental- and mimetic angle, which can be successfully clarified using MD and poromechanical model incorporating with the geothermal gradient law. As the development of computational power and physical examination level, the simulation sophistication and improvements in MD, GCMC, and other numerical models will provided more opportunities to go beyond the current informed approach, gaining our confidence in the engagement in the estimation of coal swelling deformation behaviors. These reactive MD works have clarified the feasibility and capability of ReaxFF to descript the initial reactive events for coal pyrolysis and combustion. In future, advancing MD simulation will allow the exploration of the more complex reaction process. The reaction mechanism of the pyrolysis and spontaneous combustion should also be a positive trend, as well as the potential of MD for both visualization and microscopic mechanisms for more clean utilization process of coal. Thus, it is expected that the availability of MD will continue to increase and be added to the extensive list of advanced analytical approaches to explore the multi-scaled behaviors in coalbed methane geology.